2012
DOI: 10.1038/aps.2012.135
|View full text |Cite
|
Sign up to set email alerts
|

The effect of poor compliance on the pharmacokinetics of carbamazepine and its epoxide metabolite using Monte Carlo simulation

Abstract: Aim: To study the effects of delayed and missed doses (poor compliance) on the pharmacokinetics of carbamazepine (CBZ) and its main active metabolite carbamazepine-10,11-epoxide (CBZE) in Chinese epilepsy patients using Monte Carlo simulation. Methods: CBZ and CBZE time-concentration profiles in various scenarios were generated based on a population pharmacokinetic study in Chinese epilepsy patients using Monte Carlo simulation. The scenarios included patients given multiple doses of CBZ that ranged from 100 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…A preclinical study of BCP indicated that the drug only attenuated pain behavior at an early stage (from d 4 to d 6) by inhibiting microglia [44] ; however, an increasing number of therapeutic effects of the agent have been identified. In studies of CIPN, minocycline prevented CIPN-related symptoms and the activation of astrocytes despite the lack of microglial activation indicators [16][17][18][19] .…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
“…A preclinical study of BCP indicated that the drug only attenuated pain behavior at an early stage (from d 4 to d 6) by inhibiting microglia [44] ; however, an increasing number of therapeutic effects of the agent have been identified. In studies of CIPN, minocycline prevented CIPN-related symptoms and the activation of astrocytes despite the lack of microglial activation indicators [16][17][18][19] .…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
“…Computer simulation is a cost-effective means of systematically evaluating many different permutations of drug administration and has been used to evaluate the PK impact of irregular dosing for several AEDs in order to determine appropriate corrective actions [15][16][17][18][19]. For ease of illustration, the concentration-time profiles presented in our analysis depict the "typical patient" based on the population mean for each dosing scenario, similar to simulations comparing XR and IR formulations of lamotrigine [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous retrospective comparison, risk of seizure requiring hospital or emergency admission was 21% higher (hazard ratio = 1.205, P = .002) in nonadherent patients when compared to adherent patients . In addition, inappropriate resumption dose selection may result in higher than necessary drug concentrations and is a potential concern for toxicity . Although less frequent daily dosing typically results in better adherence (ie, QD dosing relative to higher dosing frequencies), delayed or missed doses can still be expected to occur in the treatment of epileptic patients.…”
mentioning
confidence: 99%
“…Adherence to the prescribed AED regimen is an important issue in the control of seizures . The reported magnitude of nonadherence has ranged from 26% in the United States to 67% in Nigeria .…”
mentioning
confidence: 99%